Effectiveness of Homoeopathic Medicines in LM Potencies Vis-A-Vis Centesimal Potencies in Management of Cases of Essential Hypertension in Adults - A Clinical Study (Advancements in Homeopathic Research, 2022)
Objective: To compare the effectiveness of individualized homoeopathic medicines in LM potencies and Centesimal Potencies in managing the cases of essential hypertension in adults by comparing the lowering of Blood Pressure in between groups, to compare the pre and post treatment Quality of Life scores between two groups using WHO QOL BREF. Materials and Methods: A randomized parallel group clinical trial was conducted at Dr. Madan Pratap Homoeopathic Hospital, Jaipur from July 2016 to June 2017, in which 120 cases of Essential hypertension were randomly allocated to the two groups, Centesimal potency group (60 cases) and LM potency group (60 cases) treated with individualized homoeopathic medicine. Potency selection, dosage and repetition of medicine were done according to the guidelines. The outcome measures were Lowering of Blood pressure and Quality of life (WHO QOL BREF) after 3m of treatment. Results:120 cases of Essential hypertension were treated with homeopathic medicine. After three months treatment the mean Systolic Blood Pressure (SBP) reduction was 23.767 mm Hg (95%CI 21.083, 26.450) in the CENTESIMAL potency group and SBP reduction was by 27.233 mm Hg (95% CI 24.219, 30.248)) in the LM potency group. Similarly, the mean Diastolic Blood Pressure (DBP) in the CENTESIMAL potency group reduced by 12.933 mm of Hg (95%CI 11.458, 14.408) and by 13.4 mm of Hg (95% CI 11.738, 15.062) in the LM potency group. In Group A, 45 (37.5%) cases were improved, and 15 (12.5%) cases were status quo; in Group B, 51 (42.5%) cases were improved and 9 (7.5%) cases were status quo and no case were worse in both the groups. The most frequently prescribed medicines were Natrum muriaticum (n = 10, 8), Nux-vomica (n = 8, 9), Lachesis (n = 8, 3), Sepia (n = 5, 8), and Lycopodium (n = 6, 5).
Keywords: Centesimal; Essential hypertension; Homoeopathy; LM; Quality of life